2000
DOI: 10.1046/j.1365-2842.2000.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical rest and closest speech positions in the determination of occlusal vertical dimension

Abstract: Two subject groups had their mandibular positions determined, using an electrognathograph, at the clinical rest position (CRP) and at the closest speaking position (CSP). They were classified into a toothwear (largely of attritional origin) group (n=30) and a non-toothwear, or normal, group (n=60). The mean CRP deduced for the groups was similar in all three dimensions and found to be just less than 2 mm open from and 0.6 mm posterior to intercuspal position (IP) and approximately in the midline. The CSP, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 13 publications
1
15
0
9
Order By: Relevance
“…It was stated that the closest speaking space is greater than the FS in dentate subjects 10,14 . Similarities between SSS and FS were shown in several studies 3,8,12,21 . However, no previous report showed that the FS was greater than the SSS.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It was stated that the closest speaking space is greater than the FS in dentate subjects 10,14 . Similarities between SSS and FS were shown in several studies 3,8,12,21 . However, no previous report showed that the FS was greater than the SSS.…”
Section: Discussionsupporting
confidence: 78%
“…Functional adaptation was also shown for a group of subjects with severe toothwear. A cross-sectional study found that the closest speaking space in this group was reduced in comparison with that in a control group 3 . In other words, this reflects an adaptation to a slowly modified incisal relationship.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, as other studies reported broad variations in the values registered in one and the same individual by the different methods [10,29,35], none of the methods could be given preference to date [11,43]. Other authors showed that the mandibular position while speaking specific consonants (speaking space) approximates the rest position very closely and is more readily reproducible [6,7,25,42].…”
Section: Introductionmentioning
confidence: 99%
“…De geringste interocclusale spraakafstand bleek echter meer te variëren dan de fysiologische rustpositie. Burnett (2000) toonde aan dat bij patiënten met occlusale gebitsslijtage de geringste interocclusale spraakafstand kleiner was dan bij patiënten zonder gebitsslijtage, vermoedelijk doordat patiënten neuromusculair adapteren aan de ontstane situatie. Het gebruiken van de s-klanken voor het bepalen van de occlusale verticale dimensie bleek dan ook minder betrouwbaar dan voorheen werd aangenomen (Rivera-Morales en Goldman, 1997).…”
Section: Belang Van Verticale Dimensieunclassified